2018
DOI: 10.1145/3148149
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Scaling Web Applications in Clouds

Abstract: Web application providers have been migrating their applications to cloud data centers, attracted by the emerging cloud computing paradigm. One of the appealing features of the cloud is elasticity. It allows cloud users to acquire or release computing resources on-demand, which enables web application providers to automatically scale the resources provisioned to their applications without human intervention under a dynamic workload to minimize resource cost while satisfying Quality of Service (QoS) requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
152
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(166 citation statements)
references
References 99 publications
0
152
0
5
Order By: Relevance
“…Grey-box models are hybrid approaches that use models in combination with machine learning (Gandhi et al, 2012). (Qu et al, 2016) Rule-based approaches are used in commercial auto-scaling systems such as (Amazon AWS AutoScaling service,2018) or (RightScale, 2018). An advantage of this approach is that a DevOps user can relatively easily create and understand them.…”
Section: Adaptation Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Grey-box models are hybrid approaches that use models in combination with machine learning (Gandhi et al, 2012). (Qu et al, 2016) Rule-based approaches are used in commercial auto-scaling systems such as (Amazon AWS AutoScaling service,2018) or (RightScale, 2018). An advantage of this approach is that a DevOps user can relatively easily create and understand them.…”
Section: Adaptation Implementationmentioning
confidence: 99%
“…The above mentioned special characteristics of each mode of adaptation indicate that research is required by application developers in order to formulate the correct criteria to trigger adaptations. A relevant survey, which examines many scaling techniques used by dedicated software (auto-scaling) has been compiled by (Qu et al, 2016) …”
Section: Scale Up -Scale Downmentioning
confidence: 99%
“…Similarly, the optimal methodologies such as MPC and LLC based approaches are also blamed for their computationally expensive nature due to solving complex optimization models [103] despite their ability of producing optimal results. For example, Ali-Eldin et al [33] reported that for the LLC based solution proposed in [34], it takes half an hour for computing the elasticity decision for a system consist of 60 virtual machines hosted by 15 physical servers.…”
Section: Discussion Issues and Challengesmentioning
confidence: 99%
“…On the other hand, knowledge-based control solutions utilizing machine learning [67,106,107] or neural networks [99,108] provide high levels of flexibility and adaptivity. However, such flexibility and adaptivity come at the cost of long training delays, poor scalability, slower convergence rate, and the impossibility of deriving stability proof [7,18,103,109].…”
Section: Discussion Issues and Challengesmentioning
confidence: 99%
See 1 more Smart Citation